2020
DOI: 10.21608/bvmj.2020.41010.1261
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile of Frozen Chicken Meat Cuts at Qalubiya Governorate Markets

Abstract: The study was conducted on 100 random samples of frozen chicken meat cuts represented by chicken wings, drumstick, thigh and breast (25 of each) purchased from different markets at Qalubiya Governorate, Egypt. The collected samples were bacteriological examination to investigate the bacteriological quality. The obtained results cleared that the mean values of APC, psychrotrophs; coliforms and S. aureus counts (CFU/g) of the wing samples were the most contaminated with such bacterial groups followed by drumstic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Referring to the recorded results of APC (CFU/g), nearly similar results were reported by (Hassanin,et al [21]) (6.13x10 4 CFU/g in breast samples, while it is considered lower than the current obtained results for drumstick and thigh (7.47x10 4 , 6.51x10 4 ); (Shaltout,et al [22]) (5.9x10 5 and 7.1x10 5 in breast and thigh samples, respectively). While higher results were recorded by (Wahbah [23]) (5.5x10 6 and 6.8x10 6 for breast and thigh samples, respectively), and (Hassanin, et al [24]) (8.16x10 5 , 7.85x10 5 , 6.76x10 5 and 5.58x10 5 in wings, drumsticks, thigh and breast samples, respectively). On the other hand, lower counts were reported by (Atia [25]) (9.28x10 3 and 2.91x10 4 in breast and thigh samples, respectively), and (Hosny, et al [26]) (2x10 4 and 6x10 3 in drumstick and wing samples, respectively).…”
Section: Discussionmentioning
confidence: 72%
“…Referring to the recorded results of APC (CFU/g), nearly similar results were reported by (Hassanin,et al [21]) (6.13x10 4 CFU/g in breast samples, while it is considered lower than the current obtained results for drumstick and thigh (7.47x10 4 , 6.51x10 4 ); (Shaltout,et al [22]) (5.9x10 5 and 7.1x10 5 in breast and thigh samples, respectively). While higher results were recorded by (Wahbah [23]) (5.5x10 6 and 6.8x10 6 for breast and thigh samples, respectively), and (Hassanin, et al [24]) (8.16x10 5 , 7.85x10 5 , 6.76x10 5 and 5.58x10 5 in wings, drumsticks, thigh and breast samples, respectively). On the other hand, lower counts were reported by (Atia [25]) (9.28x10 3 and 2.91x10 4 in breast and thigh samples, respectively), and (Hosny, et al [26]) (2x10 4 and 6x10 3 in drumstick and wing samples, respectively).…”
Section: Discussionmentioning
confidence: 72%
“…In a study by Mohammed (37), fresh chicken thigh samples were found to be more contaminated according to the mean values of the APC and Enterobacteriaceae. Hassanin et al (38) reported that the psychrotrophic counts of wing and breast samples were 4.91 × 10 5 and 3.88 × 10 5 CFU/g, respectively, which indicated that the wings were the most contaminated samples and that breast samples had the lowest contamination. Fresh chicken meat may be contaminated with different food pathogens due to personal unhygienic culpabilities that occur during various slaughter, storage, transportation, and handling processes, including contaminated water, gastrointestinal contamination, and air, dust, sewage, and environmental surfaces (39).…”
Section: Microbiological Status Of Raw Chicken Breast and Thigh Musclesmentioning
confidence: 99%